2022
DOI: 10.1111/jcmm.17277
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐faceted role of pyroptosis mediated by inflammasome in liver fibrosis

Abstract: Liver fibrosis is a reversible pathological overreaction during the self‐repair of liver injuries, and it is the common period of chronic liver diseases induced by different pathogenesis progress into cirrhosis and even hepatocellular carcinoma. Pyroptosis, a novel form of programmed cell death, is reported to take part in the pathogenesis and progression of acute or chronic liver diseases and liver fibrosis. Caspase‐1 dependent canonical pathway and caspase‐4/‐5/‐11 mediated noncanonical pathway are the two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Pyroptosis, a recently identified form of programmed cell death, exists exclusively in dendritic cells and macrophages [ 8 ]. Moreover, it occurs in other organs, including the liver [ 9 ] and kidneys [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pyroptosis, a recently identified form of programmed cell death, exists exclusively in dendritic cells and macrophages [ 8 ]. Moreover, it occurs in other organs, including the liver [ 9 ] and kidneys [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a large proportion of patients still do not have adequate treatment, and understanding the mechanisms of the proinflammatory pathway in AILDs and potential new therapeutic approaches is critical. Experimental studies on AILDs have repeatedly demonstrated that the inflammasome is essential for the development of liver fibrosis and damage as a result of chronic inflammation ( 202 ). According to the latest available dta, dimethyl fumarate, cucurbitacin E, paeoniflorin, MCC950, IDN-7314, and geniposidic acid could inhibit the activation of NLRP3 inflammasome and the secretion of IL-1β, while bongkrekic acid and schisandra phenol B could inhibit the activation of APAF-1 and GSDME-dependent pyroptosis, thereby alleviating liver inflammatory damage in AILDs mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…LPS then binds to procaspase‐4, procaspase‐5, and procaspase‐11 and cleaves them. Activated caspase‐4, ‐5, and ‐11 then hydrolyze GSDMD, and the resulting GSDMD‐N induces cell membrane perforation and activates the receptor pannexin‐1 to open the cell membrane channels, resulting in the efflux of P2X7, ATP, HMGB1, K + , and lactate dehydrogenase (LDH); release of inflammatory factors; and pyroptosis (Jorgensen & Miao, 2015; Yang et al, 2022). Caspase‐11 induces the noncanonical activation of NLRP3, which in turn induces caspase‐1 cleavage and proinflammatory factor production (Moretti et al, 2022).…”
Section: Liver Diseases and Pyroptosismentioning
confidence: 99%